EXPLORING THE EXPERIENCE OF EFL STUDENT’S THORUGH CAMPUS TEACHING PROGRAM - Saalino, Lilianti Ariyani; Shilfani; La'biran, Roni; Revisika (Publikasi dan UKI Press UKI Toraja., 2024)
The purpose of this study finds out how the experience of students who participated in the Teaching Campus Program. Researcher conducted this study used a qualitative design, purposive sampling method with interview techniques by obtained data from 3 students of the English Language Education Study Program. The result of this research is, students participating in the Teaching Campus program gain real experience in managing classes and applying learning strategies according to student conditions. They learn to create a conducive classroom atmosphere, handle distractions wisely, and build good communication with students. In addition, they also develop students' potential through non-academic activities. The teaching strategies used vary, but all aim to improve the effectiveness of learning and student understanding.